EDUKASI PENCEGAHAN DAN PENATALAKSANAAN ASMA PADA SISWA DI SMKN 2 KABUPATEN SAMPANG - Yunita Amilia; Desy Holifatus Suaida; Madinatul Musyarrofah (LPPM STAI Muhammadiyah Probolinggo, 2026)
Asthma is one of the diseases that can affect adolescents and can increase the incidence of illness among teenagers, particularly among senior high school students. One of the most common factors that trigger asthma recurrence in adolescents is smoking, along with a lack of understanding about asthma, its triggering factors, and appropriate prevention and management strategies. Many adolescents are still unaware of the importance of avoiding asthma triggers such as dust, cigarette smoke, air pollution, excessive physical activity without proper preparation, incorrect use of inhalation medications, and delays in handling asthma attacks. Increasing students’ awareness of how to prevent asthma recurrence can begin with improving their knowledge.The method used in this community service activity was educational intervention through the delivery of materials, distribution of leaflets, practical demonstrations, and evaluation of students’ knowledge using pre-tests and post-tests. The community service activity was conducted for one month, from August 27 2025 to September 26 2025 at SMKN 2 Sampang Regency. The target of this community service program was 35 tenth-grade studens of SMKN 2 Sampang. The participants were very enthusiastic about participating,in the activity. As a result of this program, the students were able to explain asthma and the impact of smoking, and they were able to correctly demonstrate the management and prevention of asthma.